(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
In this article, we discussed the medium-term development strategy of Uzbekistan on increasing the base of local budget revenues, ensuring their financial independence, and creating a competitive environment between regions. It is known that the development of the country’s economic and social processes is reflected in the expenditure of local budgets.